PERLINDUNGAN KEHIDUPAN PEREMPUAN DALAM KELUARGA DAN MASYARAKAT - Nadia, Zunly (Sunan Kalijaga State Islamic University & The Asia Foundation, 2011)
This article talks about the importance of women in the family and society, with special respect to matters of trafficking. Such trafficking cases need serious attention, due to its alarming growth. Indonesia has even been the greatest supplies in the world. The modes of its execution have become more complex and diverse. There are many reasons why trafficking is on the rise, among them matters of poverty, economy, education and others, further complicated by domestic political issues and weak governance. The Quran as a book of teachings and guidance has also spotlighting matters of trafficking (in connection with slavery at the time of the Prophet Mohammed). There are several options and steps that the Quran takes with respect to freeing people from slavery. It is therefore that it is important to consider possible tafsir against trafficking as a stopgap. As a Muslim majority nation, religion is quite influential in constructing the views of society, and perhaps such tafsir could become a basis for anti-trafficking efforts.